Changes in cochlear blood flow in mice due to loud sound exposure measured with Doppler optical microangiography and laser Doppler flowmetry - Reif, Roberto; Zhi, Zhongwei; Dziennis, Suzan; Nuttall, Alfred L.; Wang, Ruikang K. (Quantitative Imaging in Medicine and Surgery, 2013)
In this work we determined the contributions of loud sound exposure (LSE) on cochlear blood flow (CoBF) in an in vivo anesthetized mouse model. A broadband noise system (20 kHz bandwidth) with an intensity of 119 dB SPL, was used for a period of one hour to produce a loud sound stimulus. Two techniques were used to study the changes in blood flow, a Doppler optical microangiography (DOMAG) system; which can measure the blood flow within individual cochlear vessels, and a laser Doppler flowmetry (LDF) system; which averages the blood flow within a volume (a hemisphere of ~1.5 mm radius) of tissue. Both systems determined that the blood flow within the cochlea is reduced due to the LSE stimulation.